Simple fish-eye calibration method with accuracy evaluation - Hughes, Ciaran; Glavin, Martin; Jones, Edward (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2011)
In this paper, a simple fish-eye radial distortion calibration procedure is described. This method avoids costly minimisation and optimisation algorithms, and is based on trivial concentricity of three extracted points. The results show that this simplicity is at the expense of increased deviation of results (and thus increased error). However, this deviation can be reduced significantly by the use of simple averaging, such that it is only marginally greater than the current state-of-the-art.